Factors associated with referral offer and acceptance following supportive care problem identification in a comprehensive cancer service. (29th June 2018) - Skaczkowski, Gemma; Sanderson, Penelope; Shand, Melissa; Byrne, Amanda; Wilson, Carlene
Abstract: To improve understanding of the triage process following distress and problem identification and the factors associated with offer and acceptance of supportive care referrals. Review of patient records/charts at a metropolitan hospital in Melbourne, Australia. Data were collected on problem identifications from 1/1/13 to 30/6/14, including patient demographics, disease and treatment information, responses to the NCCN Distress Thermometer (DT) and Problem Checklist (PC), whether referrals to supportive care services were offered and accepted/declined. Logistic regressions examined factors associated with referral offer and acceptance. Of patients completing the DT/PC, 50.1% reported a high level of distress. Overall, 61% of patients were offered referral(s), with the majority (71%) being accepted. Referrals were more likely to be offered to patients with a greater number of problems (Odds Ratio[OR] = 1.18, 95%CI = 1.12–1.25) and higher distress (OR = 1.68, 95%CI = 1.07–2.64). Referrals were more likely to be accepted by patients with a greater number of problems (OR = 1.12, 95%CI = 1.06–1.19) and lower distress (OR = 0.58, 95%CI = 0.34–1.00). The type of problem experienced by the patient was strongly related to the type of referral they were offered. At a large metropolitan hospital with in‐house supportive care services, simple problem identification with the DT/PC enabled triage to services that reflected patients' needs. The findings suggest that clear referral pathways and an organisational emphasis on supportive care may facilitate service use.